2023
DOI: 10.1007/s10143-023-02032-1
|View full text |Cite
|
Sign up to set email alerts
|

Brain stimulation for chronic pain management: a narrative review of analgesic mechanisms and clinical evidence

Abstract: Chronic pain constitutes one of the most common chronic complaints that people experience. According to the International Association for the Study of Pain, chronic pain is defined as pain that persists or recurs longer than 3 months. Chronic pain has a significant impact on individuals’ well-being and psychosocial health and the economy of healthcare systems as well. Despite the availability of numerous therapeutic modalities, treatment of chronic pain can be challenging. Only about 30% of individuals with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 178 publications
0
6
0
Order By: Relevance
“…These methods encompass different mechanisms and stages of the condition. Several of them include: gene therapy, pharmacotherapy, neuroprotection, physical intervention, bioengineering, neurorehabilitation, or cell therapy that directly affects cells (including the astrocytes) [250][251][252][253]. The activity of astrocytes in the pathogenesis of traumatic spinal cord and brain injuries is being used as a basis for developing healing methods [149,254].…”
Section: Astrocytes As a Therapeutic Option In Tbimentioning
confidence: 99%
“…These methods encompass different mechanisms and stages of the condition. Several of them include: gene therapy, pharmacotherapy, neuroprotection, physical intervention, bioengineering, neurorehabilitation, or cell therapy that directly affects cells (including the astrocytes) [250][251][252][253]. The activity of astrocytes in the pathogenesis of traumatic spinal cord and brain injuries is being used as a basis for developing healing methods [149,254].…”
Section: Astrocytes As a Therapeutic Option In Tbimentioning
confidence: 99%
“…In RINCE, electrodes attached to the patient’s scalp generate a specific current frequency, allowing the current to penetrate deeper into the cortex by reducing the impedance of the skin and skull ( O'Connell et al, 2018 ), potentially leading to improved stimulation effects. There are limited reports on RINCE therapy, and its adverse effects include transient mild head discomfort and localized cutaneous reactions ( Szymoniuk et al, 2023 ). In an RCT investigating RINCE therapy for fibromyalgia control, it was found that mean pressure points and pressure pain thresholds improved in the active treatment group compared to the sham treatment group ( Hargrove et al, 2012 ).…”
Section: Profiles Of Several Non-invasive Brain Neurostimulation Tech...mentioning
confidence: 99%
“…Deep Brain Stimulation (DBS) consists in the surgical implantation of thin electrodes within specific area of the brain to be stimulated. In case of chronic pain, electrodes are generally positioned in the PAG, in the periventricular gray matter, the ventralposterior medial or the ventral posterior lateral nuclei of the thalamus (contralateral to the side of pain), the anterior cingulate cortex or the posterior insula [ 75 , 76 ]. The positioning generally required a frame-based or frame-less stereotactic technique, targeting the area with a magnetic resonance imaging on the day before surgery and, in some centers, with intraoperative microelectrode recordings.…”
Section: Introductionmentioning
confidence: 99%